Proposing the Model to Accelerate SMEs to Apply Green Economy Practices Through the Utilization of Social Crowdfunding - Maria, Maya; Ngarbingan, Hubertina Karolina; Ginting, Ginta; Ismulyati, Sri (Yayasan Sinergi Kawula Muda, 2024)
Following Indonesia's commitment to promoting the achievement sustainable consumption and production practices (RCP- SDGs Number 12), a plan must be put in place to motivate important players (SMEs) to support the green economy. The limitations of SMEs in terms of funding to be able to implement green economic practices are accommodated through access to financial technology, namely social crowdfunding. To gain insight into how SMEs implement green economic practices by utilizing social crowdfunding, a survey was conducted on 75 SMEs use descriptive research design. The results of the descriptive analysis found that some SMEs have not been able to take advantage of social crowdfunding due to several reasons: not being able to access the right website, having requirements that are difficult to fulfill and their technology skills are not yet good. An interesting insight that was extracted from the results of this survey is the high level of confidence among SMEs that implementing green economic practices using social crowdfunding can improve business performance and are confident that they can overcome all difficulties. The proposed conceptual model can apparently be supported by research results which produce the proposition namely: